The Influence of Parent’s Perception and Involvement in Purchasing Decision of Toys For Children - Milatul Ulfa; Moh Djemjem Djamaludin (Journal of Consumer Sciences, 2016)
Toys are "the closest children’s friend" and become an integral part of their play world. Toys are a source of joy for children, but they can be risky and dangerous. This study aimed to analyze the influence of family characteristics, perception, and parental involvement on purchasing decision of toys for children. This study used cross-sectional study design. The location was chosen purposively involving two pre-schools. The samples were 200 parents who had ever bought toys. The husband or wife as decision makers in purchasing toyswas interviewed using a structured questionnaire to collect information in the decision to purchase toys. The results showed that the perception of toys had a positive and significant relationship with the involvement on purchasing decision of toys for children. Perception of toys also had influence on purchase frequence.Key words: involvement, perception,purchasing decision, toysProduk mainan anak adalah “teman terdekat” anak dan menjadi bagian yang tidak terpisahkan dari anak-anak dalam bermain. Mainan anak merupakan sumber kegembiraan bagi anak, namun justru dipenuhi dengan resiko dan bahaya. Penelitian ini bertujuan untuk menganalisis pengaruh karakteristik keluarga, persepsi dan keterlibatan orangtua terhadap keputusan pembelian produk mainan anak. Desain penelitian ini menggunakan cross sectional study. Pemilihan lokasi penelitian dilakukan secara purposif dengan melibatkan dua Taman Kanak-kanak (TK). Melibatkan 200 orang tua yang pernah membeli produk mainan anak. Suami atau istri sebagai pengambil keputusan dalam pembelian produk mainan anak diwawancarai dengan menggunakan kuesioner terstruktur untuk menggali informasi keputusannya dalam pembelian produk mainan anak. Hasil penelitian menunjukkan bahwa persepsi mengenai produk mainan anak mempunyai hubungan positif dan signifikan dengan keterlibatan orang tua dalam memutuskan pembelian produk mainan anak. Terdapat pengaruh persepsi mengenai produk mainan anak terhadap frekuensi pembelian.Kata kunci: keputusan pembelian produk mainan anak, keterlibatan, persepsi, produk mainan anak